Findings of Hypotension in Spinal Anesthesia Patients with Lumbar 3-4 And Lumbar 4-5 - Amir, Melani Setiaputri; Triyudono, Danang; Suandika, Made (Global Indonesia Health Care (GOICARE), 2024)
Background: Hypotension is a common complication associated with spinal anesthesia, often resulting from sympathetic nerve block. Factors such as the type of drug, patient positioning, injection site, dosage, and age influence the incidence of hypotension. Purpose: This study aimed to evaluate the incidence of hypotension in patients receiving spinal anesthesia at the lumbar 3-4 (L3-L4) and lumbar 4-5 (L4-L5) injection sites. Methods: A quantitative descriptive study with a cross-sectional approach was conducted, involving 190 respondents selected via purposive sampling. Univariate data analysis was performed. Findings: Findings indicated that patients receiving spinal anesthesia at the L3-L4 site experienced an average systolic blood pressure decrease of 24.69% and a diastolic decrease of 16.17%. In contrast, patients with L4-L5 injections showed a lesser reduction, with systolic pressure dropping by 15.51% and diastolic pressure by 12.31%. Additionally, the pulse rate decreased progressively within the first 20 minutes following induction. The average pulse rate at the 20th minute was 75.06 for patients with L3-L4 injections and 75.65 for those with L4-L5 injections. Conclusion: The study highlights that the incidence of hypotension varies based on the spinal injection site, with more significant decreases in blood pressure observed in patients receiving injections at L3-L4 compared to L4-L5. These findings have important implications for anesthesia management in clinical practice.